(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The article on the topic "The future of military pedagogy" describes the current aspects of modern military pedagogy and the requirements for future military pedagogy. This article highlights the ways of solving the training of military pedagogy in the future, in contrast to the training of a modern teacher and the questions posed to them The information considered in this article has been studied from a source that considers topical issues of modern pedagogy and the tasks of training a teacher in the future, and the information is of an individual opinion and character.